‘Where Is the Structure? The Ecological Foundations of Voters’ Consistency’: PhD by Marta Gallina (UCLouvain), supervisors: Pierre Baudewyns and Ruth Dassonneville (UdeM) - Luartz, Lewis Alexander (Politics of the Low Countries, 2025)
Are citizens politically sophisticated? In other words, are they competent about politics? This is an important question given the implications for a negative response: if citizens are not politically sophisticated, how can they be expected to make decisions at the ballot box? Indeed, this issue is crucial for both scholars and anyone who cares about and promotes democratic principles. In fact, democracies tout the idea that elections are important for choosing officials, who in turn run almost every aspect of society. From fixing roads to establishing and collecting taxes and tariffs, the standard by which a democratic system is considered well-functioning is dependent on citizens and their capacity to make decisions at the ballot box. But what if the average citizen does not know anything about politics? This seems problematic as it suggests uninformed decisions are made come election time. If this is the case, then is democratic rule simply rule by the worst class? Or perhaps it is, as Aristotle would suggest in The Politics, that democracy is one of the ‘defective and perverted forms’ of government? The implications associated with a lack of political sophistication are quite clear and, unfortunately, much of the literature suggests that citizens are not politically sophisticated.